CHI3L1 polymorphisms, cord blood YKL-40 levels and later asthma development. Issue 1 (December 2016) - Usemann, Jakob; Frey, Urs; Mack, Ines; Schmidt, Anne; Gorlanova, Olga; Röösli, Martin; Hartl, Dominik; Latzin, Philipp
Abstract Background Single nucleotide polymorphisms (SNPs) in chitinase 3-like 1 (CHI3L1 ), the gene encoding YKL-40, and increased serum YKL-40 levels are associated with severe forms of asthma. It has never been addressed whether SNPs inCHI3L1 and cord blood YKL-40 levels could already serve as potential biomarkers for milder forms of asthma. We assessed in an unselected population whether SNPs inCHI3L1 and cord blood YKL-40 levels at birth are associated with respiratory symptoms, lung function changes, asthma, and atopy. Methods In a prospective birth cohort of healthy term-born neonates (n = 260), we studiedCHI3L1 polymorphisms, and measured cord blood YKL-40 levels by ELISA in (n = 170) infants. Lung function was performed at 5 weeks and 6 years. Respiratory health during the first year of life was assessed weekly by telephone interviews. Diagnosis of asthma and allergic sensitisation was assessed at 6 years (n = 142). Results The SNP rs10399805 was significantly associated with asthma at 6 years. The odds ratio for asthma was 4.5 (95 % CI 1.59–12.94) per T-allele. This finding was unchanged when adjusting for cord blood YKL-40 levels. There was no significant association for cord blood YKL-40 levels and asthma. SNPs inCHI3L1 and cord blood YKL-40 were not associated with lung function measurements at 5 weeks and 6 years, respiratory symptoms in the first year, and allergic sensitisation at 6 years. Conclusion Genetic variation inCHI3L1 might be related to the development of milder forms of asthma. Larger studies are warranted to establish the role of YKL-40 in that pathway.